Prevalence of Gastric and Small-Intestinal Mucosal Injury in Elderly Patients Taking Enteric-Coated Aspirin by Magnetically Controlled Capsule Endoscopy - Feng Gao; Xue Chen; Jie Zhang (Gastroenterology Research and Practice)
Objective. To investigate aspirin-related gastric and small-intestinal mucosal injury in elderly patients by magnetically controlled capsule endoscopy (MCCE). Methods. Patients taking enteric-coated aspirin attending the outpatient department of Beijing Anzhen Hospital, Capital Medical University, from September 2017 to July 2019 underwent MCCE to assess injury to the gastric and small-intestinal mucosa. The patients were divided into the elderly group (age≥60 years) and middle-aged group (45 years≤age<60 years), and their clinical data were evaluated. Results. Sixty-eight patients (34 per group) taking enteric-coated aspirin were recruited, and the elderly and middle-aged groups did not differ significantly in sex, history of smoking, history of alcohol consumption, body mass index, or accompanying diseases. In the elderly and middle-aged groups, the gastric Lanza scores were 2.0 (2.0, 3.0) and 2.0 (1.0, 3.0; P=0.192), the numbers of patients with small-intestinal mucosal injuries (at least one erosion and/or ulcer) were 30 (88.2%) and 15 (44.1%; P<0.001), the numbers of patients with more severe small-intestinal mucosal injuries (larger erosion and/or ulcer) were 11 (32.4%) and 3 (8.8%; P=0.033), the numbers of patients with ileal erosion were 22 (64.7%) and 8 (23.5%; P=0.001), and the durations of aspirin use were 30.0 (12.0, 120.0) and 10.5 (2.0–48.0) months (P=0.007), respectively. Conclusions. The rate of small-intestinal mucosal injury was significantly higher in elderly than in middle-aged patients taking enteric-coated aspirin, especially the rate of ileal erosion. MCCE enables the monitoring of aspirin-related gastric and small-intestinal mucosal injury in elderly patients, which can guide treatment decision making.